Palladium-Catalyzed Cycloisomerization of 2‑Ethynylbiaryls to 9‑Methylidene Fluorenes - Guo, Hongyu; Zhang, Sheng; Feng, Xiujuan; Yu, Xiaoqiang; Yamamoto, Yoshinori; Bao, Ming (Organic letters, 2022)
A palladium-catalyzed cycloisomerization of 2-ethynylbiaryls to 9-methylidene fluorenes is described for the first time. The cycloisomerization of 2-ethynylbiaryls proceeded smoothly in the presence of weak acid at low temperature to afford 9-methylidene fluorenes in satisfactory to high yields. This new type of cycloisomerization of 2-ethynylbiaryls is operationally simple and scalable and exhibits high functional-group tolerance. Various synthetically useful functional groups, such as halogen atoms, as well as formyl, acetyl, methoxycarbonyl, cyano, and nitro groups, remain intact during the cycloisomerization of 2-ethynylbiaryls.